Nurses' readiness to prescribe under supervision in Saudi Arabia: A cross-sectional study - Monir M. Almotairy; Amal T. Alghamdi; Ali M. Alzahrani; Mohammed S. Alqarni; Sultan A. Alghamdi; Mohammed A. Alshahrani (Elsevier, 2023)
Aim: To explore nurses' readiness to prescribe medications under supervision and identify associations between prescribing practices under supervision and demographic characteristics in Saudi Arabia. Design: A cross-sectional study. Methods: Using convenience sampling, this study used a 32-item survey to collect data on nurses prescribing medications under supervision between December 2022 and March 2023. Results: A total of 379 nurses were recruited from different regions in Saudi Arabia. Approximately 7% (n = 30) of the participants were prescribing medications independently, and 70% (n = 267) expressed their likelihood of becoming prescribers. The highest motivating factors to become prescribers were improvement of patient care (52.2%) and contribution to the multidisciplinary team (52.0%). Most participants (60%-81%) agreed that prescribing medications under supervision would improve potential outcomes at the system, nurse, and patient levels. Availability of appropriate mentors or supervisors (72.9%) was the highest rated facilitating factor, followed by support of nursing colleagues (72%). Based on demographic characteristics, findings revealed significant differences in the: a) likelihood and motivators of becoming prescribers; b) required minimum qualification, years of experience, and continuing professional education hours to become prescribers; and c) type of organizations delivering educational programs for nurse prescribing. Conclusion: Majority of nurses in Saudi Arabia favored becoming prescribers, and motivating factors were mostly relevant to optimizing patient care outcomes. Having the proper supervision was rated as the most facilitating factor for nurse prescribing. Nurses' views on potential outcomes, facilitating factors, and possible motivators varied based on nurses' demographical characteristics. Implications for the professional and/or patient care: Nurses favored prescribing under supervision to improve patient care outcomes, which is an opportunity to expand the benefits of health services, including easy access to healthcare. Impact: Results revealed that nurses support the implementation of prescribing practice under supervision. Thus, the findings may inform practice change in Saudi Arabia to allow prescribing under supervision, which was perceived to have a positive impact on patient care outcomes. Reporting Method: This study adhered to STROBE guidelines.